Rzecz o edukacyjnym kłamstwie - Śliwerski, Bogusław; Kobierski, Konrad (Annales. Etyka w Życiu Gospodarczym, 2008)
The subject of the analysis is within the category of an educational lie. According to Maria Ossowska, this might be understood as either a justified or permitted misleading of someone, or the maintaining an illusion for either one’s own or another’s sake. Looking at different categories of these distortions of truth, we find that they are used not only for a child’s upbringing or the benefit of the topic, but for withholding or modifying the information about the reality or educational concept. Cheating is an example of an educational lie and it combines someone’s opinion with truth, but would be falsely incompatible with factual knowledge and truthful understanding. Pupils who cheat mislead the teacher and, in the instructor’s ignorance, are led to believe that those pupils have, in fact, knowledge reflected in the exam. Likely the teacher is being cheated as well the student for different reasons. The educational lie has another dimension (when we take into account the sham activity) the quasi teaching or the pseudo-education. This occurs when educators/teachers offer their pupils/clients something different from what should be. The pretence takes place along with the authentic process of learning or completing educational tasks.